Preconcentration of Lutetium from Aqueous Solution by Transcarpathian Clinoptilolite - Emilia Stechynska; Volodymyr Vasylechko; Galyna Gryshchouk; Ihor Patsay (Acta Chimica Slovenica, 2020)
Sorptive properties of Transcarpathian clinoptilolite towards trace amounts of Lu(III) were studied under dynamic conditions. It is shown that this lanthanide is sorbed from the weakly alkaline solution (рН 10) most efficiently. The sorption capacity of clinoptilolite under the optimal conditions is equal to 9.37 mg g-1. The distribution of various species of Lu(III) in aqueous solutions at various total concentration of the lanthanide in the pH range from 4 to 13 was calculated. The best desorbent of Lu(III) is the 1 mol L–1 solution of NaCl, preacidified with the solution of HCl to a value of рН 4.0. This desorbent enables 95–100 % of Lu(ІІІ) removal. The method of Lu(III) trace amounts preconcentration from aqueous samples in a solid phase extraction mode with the further determination of this rare earth element via the spectrophotometric method using arsenazo III was developed. The linearity of the proposed method was observed in the range of 1-12 ng mL-1 with the detection limit of 0.4 ng mL-1.